Identification of microsatellite markers associated with seed-coat darkening in common bean - Couto, Karla Rodrigues; Santos, João Bosco dos; Ramalho, Magno Antônio Patto; Silva, Graciele Simoneti da (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to indentify microsatellite markers linked to the quantitative trait loci (QTL) responsible for the late seed-coat darkening in the carioca type common bean, in order to reduce the evaluation time spent in selection for this trait. Data of seed-coat darkening of 185 F2:3 progenies derived from the cross VC-3 x 'BRSMG Majestoso', were used. Out of these data, two segregating DNA bulks were constructed to evaluate 444 SSR primers. The applicatives GQMOL and Sisvar were used to evaluate the segregations, elaborate the linkage groups, and to perform single mark and regression analysis (backward method). Eight markers were polymorphic in the DNA bulks. Six of them were mapped in a 80.49-cM linkage group. Out of these six markers, three were very close to the QTL responsible for the late grain darkening. The PVM02TC116 marker co-segregate with that QTL, and the PVESTBR-98 (2.00 cM) and PV176 (12.24 cM) ones flank it, which indicates that high efficiency in the assisted selection is possible.
Keywords: Phaseolus vulgaris; quantitative trait loci; molecular marker; assisted selection; SSR